Teaching of pharmaceutical care in Latin America: a structured review - Pedro Amariles; Edwin J. sorio-Bedoya; Diana Cardona (Elsevier, 2019)
Objective: To systematize the information available on the teaching of pharmaceutical care, at the undergraduate and postgraduate level, in Latin America describing the current situation, perspectives, challenges, and recommendations. Method: A structured review of works related to the teaching of pharmaceutical care in Latin America was made in PubMed, Scopus, Scielo, and Google Scholar, without time limit. Additionally, an internet search of study plans of the different pharmacy programs in this region and the accreditation status was performed. Results: Thirty-six publications on the teaching of pharmaceutical care were identified. In addition, information from 146 pharmacy study plans with predominance of the active teaching methodology; so 25 postgraduate studies in the healthcare area was obtained. The percentage of accredited programs was 31.8% and 37.7% for graduate and postgraduate programs, respectively. Brazil was recognized by the use of simulation, information, and communication technologies, and addition by frequency of the blended education; while Colombia by the incorporation of early practices at the healthcare level. Conclusions: The information available in publications and study plans demonstrates a growing interest in the teaching of pharmaceutical care in Latin America. However, it is necessary that universities perform integrated work with health institutions, in pro to get the accreditation of their services for teaching. Likewise, harmonize concepts and early practices that help to optimize teaching and promote the results divulgation obtained.